The determinants of capital structure of real estate companies: Evidence from China - Yao, Li (2015)
Ultimately global property markets continue to receive an increasing degree of interest from institutions, fund managers, and private investors. With real estate having formally been acknowledged as an asset class, it is receiving a strong reputation as a relative source of more stable returns, higher yields and steady cash flows. Research has proved that capital structure selections differs significantly across industries. Property industry is exclusive in diverse industries in terms of capital structure selection. This as a result of property firms have more security (real estate assets) to deal with larger amounts of debt, and usually have higher leverage ratios. Therefore, this study is important as it develops the understanding of capital structure determinants in Chinese real estate companies (REC). This study examines capital structure determinants of real estate companies in China, listed on the Shanghai Stock Exchange and Shenzhen Stock Exchange from the year 2005 until 2012. The final sample consists of 70 with a total of 561 observations. The findings clearly confirm for what has been found in other studies but in different scope. The result shows that the most powerful factor in affecting LEVERAGE decisions in the model is non-debt tax shields, profitability, tangibility and size of the companies. The result shows that non-debt tax shields is positively related to total debt for Chinese REC. Profitability is negatively significant to leverage in both models and in line with the pecking order theory. The positive relationship between tangibility and leverage gives support to the trade-off theory which postulates that tangible assets act as collateral and provide security to lenders in the event of financial distress. The size of REC companies is positively and significantly control for leverage, bigger firms can borrow at more favourable rates because they are perceived as less risky.